2011
DOI: 10.1021/ja202408w
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical Micelles of Controlled Length with a π-Conjugated Polythiophene Core via Crystallization-Driven Self-Assembly

Abstract: Solution self-assembly of the regioregular polythiophene-based block copolymer poly(3-hexylthiophene)-b-poly(dimethylsiloxane) yields cylindrical micelles with a crystalline P3HT core. Monodisperse nanocylinders of controlled length have been prepared via crystallization-driven self-assembly using seed micelles as initiators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
271
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 246 publications
(280 citation statements)
references
References 58 publications
9
271
0
Order By: Relevance
“…Following the elegant studies of crystallization-driven block copolymer self-assembly reported by Manners and Winnik [80][81][82][83][84][85], PISA syntheses of diblock copolymer nano-objects with semi-crystalline cores have been recently reported in the literature. For example, Charleux and co-workers conducted the RAFT dispersion polymerization of a bespoke cholestryl-based (meth)acrylic core-forming monomer in an ethanol/water mixture to produce well-defined diblock copolymer nanorods and nanofibers [44].…”
Section: Alternative Core-forming Blocks For Raft Alcoholic Dispementioning
confidence: 99%
“…Following the elegant studies of crystallization-driven block copolymer self-assembly reported by Manners and Winnik [80][81][82][83][84][85], PISA syntheses of diblock copolymer nano-objects with semi-crystalline cores have been recently reported in the literature. For example, Charleux and co-workers conducted the RAFT dispersion polymerization of a bespoke cholestryl-based (meth)acrylic core-forming monomer in an ethanol/water mixture to produce well-defined diblock copolymer nanorods and nanofibers [44].…”
Section: Alternative Core-forming Blocks For Raft Alcoholic Dispementioning
confidence: 99%
“…380 Furthermore, cylindrical micelles of controlled length (L n 5 72-320 nm) and low dispersity ( -D 5 1.02-1.08) with p-conjugated crystalline cores were obtained via the CDSA of poly(3-hexylthiophene)-block-poly(dimethylsiloxane) (P3HT-b-PDMS) in hexane or diethylether using seed micelles as initiators. 381 Next to the single component micelles, B-A-B triblock comicelles were obtained by CDSA using P3HT-b-PS unimers for the A block, and P3HT-b-PDMS for the B block in the multicomponent cylindrical micelles. 382 Hayward and coworkers reported the sonocrystallization of a twocomponent mixture of a perylene diimide (PDI) derivative with P3HT, which acts as a soluble crystal modifier.…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
“…6−10 Another advantage of CDSA is the easily tuned composition of the obtained nanostructures, and the dual-component or multicomponent nanostructures with different morphologies can be formed via random or block cocrystallization of the polymers with similar crystallized moieties. 11 The crystallized blocks in these polymers can be composed of poly(ferrocenyl dimethylsilane) (PFDMS), 12 poly(3-hexylthiophene) (P3HT), 13,14 poly(ε-caprolactone) (PCL), 15,16 stereoregular polylactides (srPLA), 17,18 poly(ethylene oxide), 19 polyethylene (PE), 20 and polyacrylonitrile (PAN). 21 Most of these types of block polymers can only form one-dimensional cylindrical or wormlike crystalline-core micelles through the living CDSA method.…”
Section: Introductionmentioning
confidence: 99%